Reflections on low-dose radiation, the misconceptions, reality and moving forward. (27th September 2021) - Lips, M; Anderson, E; Nakamura, T; Harris, F; Schneider, G; Zic, J; Sanders, C; Owen, J; Hondros, J; de Ruvo, A
Abstract: Low dose radiation has been widely accepted by the radiation protection community as presenting a very low risk to human health, if any. Over-conservatism in optimisation principles and regulations have resulted in a disproportionate fear of radiation amongst the general public and government authorities alike, overlooking the great benefits nuclear science and techniques have brought to society as a whole. As such, the World Nuclear Association advocates for a recontextualisation of the radiation hazards with regards to low dose radiation, and a greater awareness as to the absence of any discernible effects associated with it.